Gambaran kandungan antibiotik pada sedimen kawasan pesisir teluk Manado - Jonathan E. E. Pijoh; Henry M. F. Palandeng; Ronald I. Ottay (UNIVERSITAS SAM RATULANGI, 2021)
Introduction: Antibiotics are drugs that are often used to treat bacterial infections. Excessive use of antibiotics can lead to pollution if the residual waste from its use is not properly degraded. The residual waste that is not properly degraded will cause pollution to the environment where the antibiotic waste is released. Sometimes several sources of antibiotic usage do not have a good waste treatment system, some of which are hospitals. Hospitals must have a wastewater treatment system that is called Wastewater Treatment Plant (WWTP). A good WWTP function is to degrade all kinds of waste in the hospital, so that if it is released into the environment it will not cause harmful effects such as pollution. Sometimes there is some waste that does not go through a good waste treatment system, so it has the potential to cause pollution to the environment. Antibiotics that are not properly degraded can cause pollution to the area where the waste is disposed of, one of which is sediment in the coastal area. Aim: To determine the overview of antibiotic content in the sediments of the coastal area of Manado Bay. Method: This research is a quantitative-descriptive study. Result: It was found that there was antibiotic content in the sediment which was marked by bacteria in the sediment of the area that were resistant to several types of antibiotics.Conclusion: Based on the result, there is antibiotic content in the sediments of the coastal area of Manado Bay.Keywords: antibiotics, sediment, Manado Bay.